Structure, electronic, optical and thermodynamic behavior on the polymerization of PMMA: A DFT investigation. (February 2018) - Shah, Esha V.; Patel, Chetna M.; Roy, Debesh R.
Graphical abstract: Highlights: DFT investigation on structural and physicochemical aspects of PMMA is performed. The PMMA units belong in UV-C region with a sequential red shift during growth. The thermodynamic aspects also noticed to be in favor the polymerization process. FMOs analysis provides incisive insight on the stability during polymerization. NLO property for PMMA is understood through polarizability and hyperpolarizability. Abstract: A density functional theory based scrutiny is implemented on the structure, electronic, optical and thermodynamic properties of the Poly (Methyl MethAcrylate) polymers (PMMA or nMMA; n = 1–5). The quantum chemical descriptors, e.g. HOMO-LUMO gap, ionization potential, chemical hardness, binding energies etc. of the PMMA polymers provides the measure for the structural and electronic properties. The parameters polarizability (α) and hyperpolarizability ( β ) provides information for the non-linear optical (NLO) properties of the polymers. The absorption range of the PMMA polymer in the electromagnetic radiation spectrum during its growth is assessed by the UltraViolet-Visible (UV–vis) optical absorption spectra. To gain further insight on the origin of stability during the polymerization process, we have simulated frontier molecular orbitals (FMOs) and various thermodynamic properties, viz., entropy (S), enthalpy (H) and Gibbs free energy (G).